Dari Kelas ke Jalanan: Konsekuensi Sosial-Ekonomi Putus Sekolah terhadap Tenaga Kerja Muda - Ofianto, Ofianto; Agustin, Vanny Noer (TSAQOFAH, 2025)
Education is a fundamental element in shaping individual quality and determining one’s future direction. Beyond serving as a means to develop rational and critical thinking, education also plays a crucial role in achieving financial independence. However, not all children have equal opportunities to access formal education up to the desired level. School dropout remains a persistent issue that continues year after year and proves difficult to eradicate. The rising number of school dropouts has significant impacts, both at the individual and societal levels. Individuals who do not complete formal education often face difficulties in accessing employment opportunities and experience limitations in social and economic mobility, which can trap them in cycles of poverty. The causes of school dropout are complex, involving both internal and external factors. This article aims to analyze the social and economic implications of students’ decisions to leave school, as well as their ability to compete in a modern labor market that increasingly demands specific skills and qualifications. The study employs a qualitative method with a literature review approach, drawing data from scholarly sources, journal articles, and relevant news reports. Thematic analysis is used to gain a deeper understanding of the socio-economic dynamics that underlie and influence school dropout decisions. Keywords: